Association between cannabis use and treatment outcomes in patients receiving methadone maintenance treatment: a systematic review protocol. Issue 1 (December 2016) - Zielinski, Laura; Bhatt, Meha; Eisen, Rebecca; Perera, Stefan; Bhatnagar, Neera; MacKillop, James; Steiner, Meir; McDermid Vaz, Stephanie; Thabane, Lehana; Samaan, Zainab
Abstract Background With the non-medical use of prescription opioids increasingly becoming a method of abuse in Canada, the number of patients requiring methadone maintenance treatment (MMT) for opioid use disorder has increased dramatically. The rate of cannabis use in this population is disproportionately high (~50 %). Because its use is generally perceived as harmless, cannabis use is often not monitored during MMT. Current literature regarding the effects of cannabis use on MMT is conflicting, and the presence and nature of an association has not been clearly established. The primary objective of this review will be to conduct a systematic review of the literature and, if appropriate, a meta-analysis to determine whether there is an association between cannabis use and MMT outcomes. A secondary objective will be to perform subgroup analyses (by age, sex, method of cannabis measurement, and country) to determine whether cannabis use differentially influences MMT outcomes within these subgroups. Methods/design The search will be conducted on the following electronic databases using a predefined search strategy: MEDLINE, EMBASE, PsycINFO, and Cumulative Index to Nursing and Allied Health Literature (CINAHL). Two authors (LZ and MB) will independently screen articles using predetermined inclusion/exclusion criteria and will extract data from included articles using a pilot-tested data extraction form. Disagreements at all stages of the screening process will be settled through discussion, and when consensus cannot be reached, a third author (ZS) will be consulted. An assessment of quality and risk of bias will be conducted on all included articles, and a sensitivity analysis will be used to compare results of studies with high and low risk of bias. We will perform random- and fixed-effects meta-analyses, if appropriate, with heterogeneity calculated using theI 2 statistic and formal evaluation of publication bias. Discussion Results of this systematic review will elucidate the association between cannabis use and methadone maintenance treatment outcomes. We will provide evidence that will be useful to clinicians regarding whether monitoring cannabis use during MMT is advantageous for optimizing MMT outcomes. Systematic review registration PROSPEROCRD42015029372